2020
DOI: 10.3892/ijmm.2020.4631
|View full text |Cite
|
Sign up to set email alerts
|

TRAP1 attenuates H9C2 myocardial cell injury induced by extracellular acidification via the inhibition of MPTP opening

Abstract: Extracellular acidification leads to cardiac dysfunction in numerous diseases. Mitochondrial dysfunction plays an important role in this process. However, the mechanisms through which extracellular acidification induces mitochondrial dysfunction remain unclear. Tumor necrosis factor receptor-associated protein 1 (TRAP1) maintains mitochondrial function and cell viability in tumor and non-tumor cells. In the present study, extracellular acidification was found to induce H9C2 cell apoptosis, mitochondrial dysfun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Mitochondria is very crucial for cardiomyocytes as an energy supplier [ 17 ]. Extracellular acidosis severely impaired mitochondrial function and decreased the ATP levels of H9C2 cells in our previous study [ 16 ]. A similar study also reported that extracellular acidosis decreased mitochondrial membrane potential and induced mitochondrial permeability transition pore (mPTP) associated cell death in HEK293 cells [ 4 ].…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Mitochondria is very crucial for cardiomyocytes as an energy supplier [ 17 ]. Extracellular acidosis severely impaired mitochondrial function and decreased the ATP levels of H9C2 cells in our previous study [ 16 ]. A similar study also reported that extracellular acidosis decreased mitochondrial membrane potential and induced mitochondrial permeability transition pore (mPTP) associated cell death in HEK293 cells [ 4 ].…”
Section: Introductionmentioning
confidence: 90%
“…Furthermore, extracellular acidosis damaged heart tissue structure and induced left ventricular dysfunction in rats [ 15 ]. In our previous study, we found that extracellular acidosis damaged mitochondria and activated mitochondrial apoptosis pathway in H9C2 cells (rat myocardial cell line) in extracellular acidosis [ 16 ], which suggested that mitochondria might play an important role in extracellular acidosis-induced cardiac dysfunction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess TRAP1 protective role by mPTP opening inhibition, Guzzo et al performed a whole-cell Ca 2+ retention capacity assay, which allows a quantitative assessment of mPTP induction, and reported that Trap1 knockdown increased mPTP sensitivity to Ca 2+ in cancer cells, while Trap1 overexpression inhibited mPTP opening in mouse embryo fibroblasts (MEF) cells and protected SAOS-2 and MEF cells from mPTP opening in starvation conditions [ 6 ]. Interestingly, TRAP1 inhibition of mPTP opening was observed not only in tumor cells [ 6 , 26 ] and hypoxic cellular models [ 4 , 65 ] but also in NRK-52E kidney cells under high glucose conditions prompting oxidative stress [ 66 ], in H9C2 myocardial cells exposed to extracellular acidification [ 67 ] and in C17.2 neural stem cells [ 5 ].…”
Section: Trap1 Functions and Signaling Pathwaysmentioning
confidence: 99%
“…TRAP1 has been directly connected to PTP modulation, given that its inhibition or downregulation results in mitochondrial depolarization, cytochrome c release, and cell death, which are all features of PTP activation, while its overexpression exerts a protective effect [51]. The TRAP1-dependent PTP regulation is detectable in different pathophysiological contexts, including models of neural stem cells, kidney disease, and ischemic damage [52][53][54]. Indeed, TRAP1 is overexpressed under hypoxia [55] and protects cardiomyocytes and rat brains from hypoxic injuries and ROS-dependent pore opening upon ischemia-reperfusion [56,57].…”
Section: Cyclophilin D: a Master Ptp Regulatormentioning
confidence: 99%